Mobile health intervention for promotion of eye health literacy - Indra Prasad Sharma; Monica Chaudhry; Dhanapati Sharma; Raju Kaiti (Public Library of Science (PLoS), 2021)
Purpose Improving eye health awareness in the underserved population is a universal eye health priority. The ubiquity of cell phones and internet usage provides new and innovative opportunities for health promotion. This study evaluated the effect of mobile health intervention (text message link) to promote eye health literacy (EHL) of priority ocular morbidities. Methods This study was an intervention evaluation and employed a two-armed pre-test post-test approach. Baseline assessment on EHL was performed on 424 university students. Participants were categorised into intervention and control groups, using the 1:1 allocation ratio. The intervention and control group received a text message alone and text message with a link, respectively. EHL was assessed via a self-administered questionnaire. The primary outcome measures were changes in EHL scores between baseline and one month post-intervention. Descriptive analysis was performed to assess the cost-effectiveness of the intervention. Results With low attrition and a response rate of 95.6%, 409 responses were eligible for analysis. The mean age of the participants (49.4% males and 50.6% of females) was 19.9±1.68 years. Baseline EHL scores were low, and there was no correlation with a demographic profile (all p<0.05, CI 95%). The demographic characteristics were similar between the two groups (for all, P <0.05, CI 95%) at baseline. The EHL scores improved in both groups between the pre-and post-test assessment; however, improvements were statistically significant only in the control group. The one-month post-intervention EHL scores were also higher in the intervention group compared to the control (p≤0.001, CI 95% for all). The total cost incurred for the intervention used was 11.5 USD. Conclusion Text message link demonstrated effectiveness for improving the EHL scores; the low baseline EHL scores substantially improved with intervention. The text message link intervention is a cost-effective method and could be considered in advocating for eye health in developing countries, particularly during global emergencies.